THE EFFECT OF BUSINESS CAPITAL ON FARMERS' INCOME IN SUKATEPU VILLAGE, NAMAN TERAN DISTRICT, KARO REGENCY - Nenni Lestari Br Surbakti; Rizka Hilda Siregar; Cindy Indah Sari Br Silaban; Tasia Tabita Br Sitepu (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the effect of business capital on farmers' income in Sukatepu Village, Naman Teran District, Karo Regency. Business capital is one of the main keys in running and developing a business. Sufficient capital allows business actors to buy raw materials and carry out effective marketing. Fruit and Vegetable Farmers, Adequate capital also affects the ability to maintain product quality. For example, the use of good storage technology can reduce losses due to decay and increase product competitiveness in the market. Income is the amount of results obtained by each entrepreneur from activities carried out in a certain period of time, such as daily, weekly, monthly, or annually. In general, income includes the total income of individuals or households in that period of time. Based on these two definitions, it can be concluded that income is income received by the community that reflects their performance during a certain period. This income can be in the form of money or non-money, and can be calculated daily, monthly, or annually. This study uses SPSS data processing. Determination of the sample using Purposive Sampling of all farmers in Sukatepu village with the number of selected samples being 97 Farmers. The results of the study found that Business Capital had a significant effect on Farmer income. Thus, with high business capital, it will increase Farmer income.